2014
DOI: 10.1186/1477-7819-12-168
|View full text |Cite
|
Sign up to set email alerts
|

Who could benefit the most from using a computer-aided detection system in full-field digital mammography?

Abstract: BackgroundThe computer-aided detection (CAD) system on mammography has the potential to assist radiologists in breast cancer screening. The purpose of this study is to evaluate the diagnostic performance of the CAD system in full-field digital mammography for detecting breast cancer when used by dedicated breast radiologist (BR) and radiology resident (RR), and to reveal who could benefit the most from a CAD application.MethodsWe retrospectively chose 100 image sets from mammographies performed with CAD betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Consequently, the performance of diagnosis is limited and varies with the doctor’s experience. To surmount this limitation, a double screening scheme has been applied in some hospitals by employing an additional expert [1]. However, this scheme is expensive and time consuming.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the performance of diagnosis is limited and varies with the doctor’s experience. To surmount this limitation, a double screening scheme has been applied in some hospitals by employing an additional expert [1]. However, this scheme is expensive and time consuming.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the increased interpretation time for DBT, the total number of cases interpreted by each trainee (n ¼ 60) was smaller than the number in some similar mammography studies (range: 50-150). However, we included more readers (n ¼ 29) than are involved in comparable mammography studies (range: [10][11][12][13][14][15][16][17][18][19], to compensate for this difference [11,12,[14][15][16]. Thus, we were able to evaluate 1,740 data points (60 studies, times 29 readers), which provides similar, if not better, statistical power than prior work evaluating resident performance in mammography.…”
Section: Discussionmentioning
confidence: 87%
“…In the study by Fiona et al, the double-reading system and CAD system had similar detection rates [ 6 ]. However, another study suggested that the CAD system improved diagnostic performance and reduced assessment time [ 14 ]. An additional benefit of the CAD system is its capacity to detect microcalcification even when used by radiologists with little experience [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%